Transformation of the municipality of Cajicá in front of the process of urbanization of the territory (2019)
Cajicá, located in the department of Cundinamarca; With an extension of 53 km2, located in La Sabana de Bogotá, north of the Capital District, in the Sabana Centro province, at a distance of 39 km from Bogotá. After 11 leaders, a municipality with an accelerated urbanization process is seen with a population of 56875 inhabitants who demand services of first necessity, such as education, health, housing, domiciliary public services, recreation, culture and sport. Socio-economic and environmental planning constitute fundamental elements of the life of the Colombian municipality, which underlie the socio-political history of the country, based on administrative reforms with the entry into force of the National Constitution of 1991 De Colombia, C. P. (1991). National Constituent Assembly. Bogotá, Colombia, P6, and is reinforced in a special way, with the approval of Law 388 of 2007 on land use planning, thus strengthening local dynamics, from planning and planning to municipal dynamics, with legal and regulatory tools and instruments , which constitute the starting point of a new country, in the historical context of the late twentieth century and the port of the XXI, where also, and as an innovative and decisive element, the participation of the community in these processes begins to be recognized, as a mechanism of integration between civil society and the State, in search of the social development of the population and the economic growth of the nation.